Manejo da mancha preta dos citros através da utilização de agentes de controle biológico - Guimarães, Christiano Grëgio (Universidade Federal de São Carlos, 2012)
The citrus industry faces serious problems represented by diseases that reduce the productivity and depreciate the fruits that give the appearance thereof. Among these diseases the citrus black spot caused by Guignardia citricarpa is one of the most important. As the predominant control of this disease is related to the chemical application, the financial costs, environmental and public health of these applications, as well as the increasing restrictions on the presence of residues in fresh fruits, and the possibility of emergence of resistant strains of pathogens to fungicides, it is necessary to study new control alternatives. Therefore, this work aimed to investigate the use of biocontrol agents, under field conditions, by applications of Bacillus subtilis, Trichoderma spp., uréia e combinação dos produtos comerciais Soil-Set® + Compostaid® on the citrus leaves that fallen to the ground, in order to reduce the production of ascospores directly and, indirectly, by acceleration of the decomposition of citrus leaves. The results of this work showed the viability of such applications as a help during the disease management to control of citrus black spot.
Management of citrus black spot through the use of biological control agents
Keywords: Agroecologia; Fitopatologia; Controle biológico; Mancha preta dos citros; Citrus sinensis; CIENCIAS AGRARIAS